Study regarding the identification of the socialization level of pubertal children who practice swimming - Nedelcu Răzvan Ioan; Petre Dan Ionuț; Nicolaiciuc Natalia (Editura Univeristatii "Stefan cel Mare" din Suceava, 2023)
Allocating short time to physical education classes in the curriculum, 2 hours per week, for students who do not have inclination and skills.